Advances in Sustainable River Management Reconciling Conflicting Interests under Climate Extremes - Wałęga, Andrzej; Kuriqi, Alban (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The main objective of this Special Issue is to contribute in understanding and provide science-based knowledge, new ideas/approaches and solutions in sustainable river management, to improve water management policies and practices following different environmental requirements aspects.